Student and internet: attempt of comparative sociological research - Rubanau, Anatoly V.; Belousova, Anastasia E.; Podolyak, Egor E.; Sidorenko, Anastasia P. (Journal of the Belarusian State University. Philosophy and Psychology, 2019)
The article analyzes grade of spread for higher education of information and communications technology and interest to various kinds of them for student youth (on materials of Belarusian State University case). The main directions of involvement of students into usage of digital technologies of education are explicated. Demands of various forms of digital educational materials and forms of organization of education are represented. The possibility of combination of usage of educational potential of internet and traditional forms of education is emphasized.